Effectiveness of clinical pharmacy services: an overview of systematic reviews (2000-2010) - Rotta, Inajara (2015)
Background: Multiple reviews have evaluated the impact of pharmacist-delivered patient care on health-related outcomes. However, it is unclear which of the pharmacist-delivered interventions in these services are the most effective. Aim of the review: To gather the evidence of the impact of clinical pharmacy services on the medication use process or on patient outcomes using an overview of systematic reviews. Methods: PubMed was searched to retrieve systematic reviews published between 2000 and 2010 that assessed the impact of clinical pharmacy services on the medication use process or patient outcomes. Two independent reviewers evaluated the study eligibility and one extracted the description and results of the services. The methodological quality of each review was assessed with the R-AMSTAR tool. Results: Of the 343 potentially relevant records identified, 49 systematic reviews, comprising a total of 269 randomized controlled trials, met the selection criteria. Clinical pharmacy services that focused on specific medical conditions, such as hypertension or diabetes mellitus, revealed a positive impact of pharmacists’ interventions on patient outcomes. For other medical conditions, however, the results were inconclusive (e.g., dyslipidemia or thromboprophylaxis). Interventions that targeted medication adherence and assessed the impact of clinical pharmacy services in prescription appropriateness also produced inconclusive results because of the variability of methods used to assess both medication adherence and medication appropriateness. Conclusions: Systematic reviews that assessed clinical pharmacy services targeting specific conditions were more conclusive given that the intervention was well defined, and the measured outcomes were unequivocal and tangible. Conversely, the results were inconclusive for interventions with a broader target and with monitoring parameters that were unclearly established or inconsistently assessed across studies. These findings emphasize the need to better define clinical pharmacy services and standardize methods that assess the impact of these services on patient health outcomes.